2021
DOI: 10.1210/clinem/dgab668
|View full text |Cite
|
Sign up to set email alerts
|

Age and Hospitalization Risk in People With Type 1 Diabetes and COVID-19: Data From the T1D Exchange Surveillance Study

Abstract: Context COVID-19 morbidity and mortality are increased in type 1 diabetes (T1D), but few data focus on age-based outcomes. Objective To quantify the risk for COVID-19 related hospitalization and adverse outcomes by age in people with T1D. Design, Setting and Patients For this observational, multisite, cross-sectional study of patients with T1D and laboratory-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Few studies have addressed the association of diabetes with the severity of COVID‐19 in children and adolescents. Of note, Demeterco‐Berggren et al 22 reported a multicenter cross‐sectional study of patients with type 1 diabetes and COVID‐19 from 56 clinical centers in the United States. A total of 767 patients were analyzed, of which 415 (54%) were younger than 19 years.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have addressed the association of diabetes with the severity of COVID‐19 in children and adolescents. Of note, Demeterco‐Berggren et al 22 reported a multicenter cross‐sectional study of patients with type 1 diabetes and COVID‐19 from 56 clinical centers in the United States. A total of 767 patients were analyzed, of which 415 (54%) were younger than 19 years.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, in most cases illness duration lasted 4 to 6 days and longer duration was associated with older children ( 25 , 27 ). COVID-19 disease severity was found to be age related, with increased severity at extremely young age (< 3 months) or above 20 years, with comorbidities such as asthma and gastrointestinal conditions ( 6 ), and in adulthood above age 40 in an age-dependent manner ( 28 ). In a study of adults with T1D, only 0.2% of people were hospitalized with COVID-19 infection, similar to the rate of hospitalization in the general population ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The T1D Exchange Multi-center COVID-19 Surveillance Study collected data from endocrinology clinics that completed a retrospective chart review and submitted information to T1D Exchange via an online questionnaire for all patients with T1D at their sites who tested positive for COVID-19. 13,14 The questionnaire was administered using the Qualtrics survey platform (www. qualtrics.com version XM) and contained 33 pre-coded and free-text response fields to collect patient and clinical attributes.…”
Section: Methodsmentioning
confidence: 99%